Contact isolation is a risk factor for venous thromboembolism in trauma patients. Issue 5 (November 2015) - Reed, Christopher R.; Ferguson, Robert A.; Peng, Yiming; Collier, Bryan R.; Bradburn, Eric H.; Toms, Alice R.; Fogel, Sandy L.; Baker, Christopher C.; Hamill, Mark E.
Abstract : BACKGROUND: Contact isolation (CI) is a series of precautions used to prevent the transmission of medically significant infectious pathogens in the health care setting. Our institution's implementation of CI includes limiting patient movement to the assigned room. Our objective was to define the association between CI and venous thromboembolism (VTE) at our Level I trauma center. METHODS: Our institution's prospective trauma database was retrospectively queried for all patients admitted to the trauma service between January 1, 2011, and December 31, 2012. Data including demographics, Injury Severity Score (ISS), preexisting medical conditions, injury type, and VTE development were collected. CI status data were obtained from our institution's infection control database. χ 2 was used to examine the unadjusted relationship between CI status and VTE. As the groups were not equivalent, logistic regression was then used to examine the relationship between CI and VTE while adjusting for relevant covariates including sex, age, ISS, and comorbidities. RESULTS: Of the 4, 423 trauma patients admitted during the study period, 4, 318 (97.6%) had complete records and were included in subsequent analyses. A total of 249 (5.8%) of the patients were on CI. VTE occurred in 44 patients (17.7%) on CI versus 141 patients (3.5%) who were not isolated ( p < 0.0001; odds ratio, 6.0; 95% confidence interval, 4.1–8.6). With the use of lasso [least absolute shrinkage and selection operator] regression to adjust for patient risk factors, this relationship remained highly significant ( p < 0.0001; odds ratio, 2.61; 95% confidence interval, 1.7–4.0). CONCLUSION: CI, ISS, hospital length of stay, and cardiac comorbidity were associated with VTE. After adjustment for other risk factors, CI remained most strongly associated with VTE. Although any medical intervention may come with unintended consequences, the risks and benefits of CI in this population need to be reevaluated. Further study is planned to identify opportunities to mitigate this increased VTE risk. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III; therapeutic study, level IV.